2004
DOI: 10.1590/s0103-64402004000200011
|View full text |Cite
|
Sign up to set email alerts
|

Laser therapy in the treatment of dentine hypersensitivity

Abstract: Cervical dentine hypersensitivity is the most frequent complaint among reported odontalgias. Thus, this study evaluated the effectiveness of two types of lasers (660 nm wavelength red, and 830 nm wavelength infrared) as dentine desensitizers, as well as both the immediate and late therapeutic effects in individuals 25 to 45 years of age. A total of 40 teeth with cervical exposure were treated in 4 sessions. They were divided into 2 groups according to treatment. A 660 nm wavelength red diode laser and an 830 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
1
27

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(111 citation statements)
references
References 4 publications
1
82
1
27
Order By: Relevance
“…In previous clinical studies, several investigators have also used the VAS, because it is easily understood by patients, it is sensitive in discriminating among the effects of various types of treatments, and it thus is suitable for evaluating the pain response seen in studies of DH. 8,9,15 The results of the present clinical trial demonstrate that both the Nd:YAG and 685-nm diode lasers were effective in desensitizing hypersensitive teeth. The results particularly illustrate their effectiveness following cold air jet stimulation.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…In previous clinical studies, several investigators have also used the VAS, because it is easily understood by patients, it is sensitive in discriminating among the effects of various types of treatments, and it thus is suitable for evaluating the pain response seen in studies of DH. 8,9,15 The results of the present clinical trial demonstrate that both the Nd:YAG and 685-nm diode lasers were effective in desensitizing hypersensitive teeth. The results particularly illustrate their effectiveness following cold air jet stimulation.…”
Section: Discussionmentioning
confidence: 57%
“…The use of lasers for the treatment of sensitive teeth may be divided into two groups: lasers with moderate power outputs, one of which is the Nd:YAG laser, and low-level lasers, one of which is the 685-nm diode laser. Both the Nd:YAG laser [8][9][10][11][12][13][14] and the 685-nm diode laser [15][16][17] have been tested for the treatment of DH by many investigators. Many of them, in spite of the wide variety of methods and types of lasers used, have proven to be successful.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under normal conditions, dentin is covered by enamel or cement and does not suffer direct stimulation. However, the exposure of dentin tubules due to enamel loss by abrasion, erosion, abfraction or root surface exposure caused by gingival recession, periodontal treatment or a combination of both (2) may produce strong dentin sensitivity (3).…”
Section: Introductionmentioning
confidence: 99%
“…[9] When comparing the efficacy of the two lasers (660 nm wavelength red, and 830 nm wavelength infrared), it was found that amongst the two, 660 nm red diode laser was more effective for dentine hypersensitivity and a higher level of reduction in sensitivity was observed at the 15 and 30 min postirradiation examinations. [10] Aranha et al also showed gradual reduction in dentine hypersensitivity using low-intensity laser (660 nm/3.8 J/cm²/15 mW). [8] After surgical removal of third molars LLLT has been shown to modulate the inflammatory process, by reducing pain and swelling and promoting the repair of damaged tissues without any harmful effects.…”
Section: Clinical Applications Dentine Hypersensitivitymentioning
confidence: 94%